A compassionate‐focused therapy group approach for acute inpatients: Feasibility, initial pilot outcome data, and recommendations. (March 2014) - Heriot‐Maitland, Charles; Vidal, Joana B.; Ball, Sarah; Irons, Chris
<x xml:space="preserve">Abstract</x> Objectives This study aimed to examine the feasibility of running and evaluating a compassion‐focused therapy (CFT) group adapted for acute inpatient settings, characterized by unpredictable lengths of admission, presentations, and diagnoses. Design and methods This pilot project used a mixed methods design to assess the impact of offering CFT‐informed group sessions on an acute inpatient unit. Pre‐ and post‐session ratings of distress and calmness, and ratings of understanding and helpfulness, were gathered from participants over a 6‐month period. Semi‐structured interviews were conducted with four participants to gather their experience of the group. Results Fifty‐seven complete sets of rating measures were generated from 82 participants recruited for the study (attrition rate 30%), from a total pool of 93 inpatients attending group sessions. Pre‐ to post‐CFT session data highlighted a significant decrease in distress ratings and a significant increase in calmness ratings. A thematic analysis of four interviews identified themes relating to understanding compassion, experience of positive affect, and the experience of common humanity. Conclusions This is the first attempt to explore the effects of a CFT‐informed approach in acute mental health settings. These groups were well received by staff and patients, with some therapeutic impact despite being comparatively short and set against the background of a busy inpatient ward. These groups can be open and transdiagnostic, with stand‐alone topics and practices having positive impacts on distress and calmness. Future studies need to focus on adapting content and pacing for this group of people based on ongoing feedback from participants. Practitioner points CFT groups incorporating psychoeducation and compassion practices appear to be understandable and helpful to inpatients in acute mental health settings. CFT acute inpatient groups can be structured as open and transdiagnostic, with stand‐alone sessions, to accommodate the varied nature of acute admissions. Group topics informed by CFT – particularly the use of compassionate focusing and imagery – may reduce distress and increase calmness among inpatients. A limitation of this pilot study is that it did not use standardized outcome measures. Moreover, as this was a feasibility study, there was no control group.